THE RELATIONSHIP OF STRESS LEVEL WITH SMOKING DEPENDENCE IN TEENAGERS - Adawiah, Robiatul; Maurida, Nurul; Ali Basri, Achmad (LPPM Universitas dr. Soebandi, 2025)
Introduction: Many teenagers said that smoking was their way to cope they stress experience, smoking makes them more relaxed, and they use it as an escape when they are stressed. The nicotine in cigarettes makes teenagers addicted to it, which affects their thoughts and behaviors and leads to smoking dependence.This research aims to analyze the relationship between stress levels and smoking dependence in teenagers. Methods: This research was a quantitative research using a correlational design with a cross-sectional approach. The population of this research were X and XI grade students who smoked with a sample size of 45 respondents. The instrument in this research used a questionnaire. Univariate analysis using frequency distribution and percentage, bivariate analysis using the Spearman Rank test. Results: The percentage of stress levels was (40.0%) detected to experience mild stress and (48.9%) detected to have moderate smoking dependence. From the spearmen rank analysis, the p-value (0.000) < α (0.05) with contingency coefficient value is 0.526, meaning that there is a strong relationship between stress levels and smoking dependence.Conclusions : Smoking dependence in teenagers can be reduced by reducing stress levels in teenagers so that teenagers are expected to manage stress well so as not to increase smoking dependence in teenagers.